Comparative morphology of the seminal receptacles of Ocypode quadrata (Fabricius, 1787) (Brachyura, Ocypodoidea) - López-Greco, Laura S.; Fransozo, Vívian; Negreiros-Fransozo, Maria Lucia; Santos, Daniela Carvalho Dos (Zootaxa, 2009)
The seminal receptacles of the Eubrachyura are an ecto-mesodermic differentiation of the genital ducts where the spermatophores are stored and fertilization takes place. The position in which the oviduct is connected to the seminal receptacles varies among species and two types, dorsal and ventral, can be distinguished. The dorsal type is frequently observed in the “soft mating system” species, while the ventral one is usually related to the “hard mating system” species. The seminal receptacles (SR) of Ocypode quadrata (Fabricius, 1787) are paired, spherical and opalescent structures with a ventral connection to the oviduct and without any differences between the two members of the pair. The SR present macroscopic features that resemble other semi-terrestrial species of Ocypodoidea and Grapsoidea, but some histological characters resemble more aquatic species such as the Majoidea. The mesodermic portion of the SR is delimited by a cubic-flat secretor epithelium with three layers of muscular cells and surrounded externally by a simple capsule of conjunctive tissue. The transition between the mesodermic and the ectodermic areas is abrupt and characterized by a folded epithelium resembling that described for some Majoidea and the presence of a high cuticular layer. Only free spermatozoa were found, but no differentiated spermatophore packages or spermatophores.